2014
DOI: 10.1039/c3cp53815j
|View full text |Cite
|
Sign up to set email alerts
|

Mode-specific vibrational relaxation of photoexcited guanosine 5′-monophosphate and its acid form: a femtosecond broadband mid-IR transient absorption and theoretical study

Abstract: UV-pump/broadband-mid-IR-probe transient absorption (TA) experiments and ab initio quantum mechanical (QM) calculations were used to investigate the photophysics in heavy water of the neutral and acid forms of guanosine 5'-monophosphate (GMP and GMPD(+), respectively). Excited GMP undergoes ultrafast internal conversion (IC) and returns to the electronic ground state in less than one picosecond with a large amount of excess vibrational energy. The spectroscopic signals are dominated by vibrational cooling - a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 76 publications
2
36
0
Order By: Relevance
“…The mode-specific vibrational energy transfer model proposed by Nielsen and co-workers [155,181] is further supported by the recent studies of Kohler and co-workers [152,154]. These authors investigated the vibrational relaxation dynamics of guanosine 5 0 -monophosphate by femtosecond broadband transient absorption spectroscopy in the 1,400-1,750 cm À1 probe region in deuterated aqueous buffer solution (pD ¼ 7.2) [154].…”
Section: Vibrational Cooling Dynamics In the Ground Statementioning
confidence: 82%
See 1 more Smart Citation
“…The mode-specific vibrational energy transfer model proposed by Nielsen and co-workers [155,181] is further supported by the recent studies of Kohler and co-workers [152,154]. These authors investigated the vibrational relaxation dynamics of guanosine 5 0 -monophosphate by femtosecond broadband transient absorption spectroscopy in the 1,400-1,750 cm À1 probe region in deuterated aqueous buffer solution (pD ¼ 7.2) [154].…”
Section: Vibrational Cooling Dynamics In the Ground Statementioning
confidence: 82%
“…These authors investigated the vibrational relaxation dynamics of guanosine 5 0 -monophosphate by femtosecond broadband transient absorption spectroscopy in the 1,400-1,750 cm À1 probe region in deuterated aqueous buffer solution (pD ¼ 7.2) [154]. In agreement with earlier studies [153,181,190], the authors found that the bleach recovery signals of the ν N3C4 + ν amino (1,517 cm À1 ) and the ν CO (1,662 cm À1 ) vibrational modes are dominated by dynamics that occur on the ground state potential energy surface.…”
Section: Vibrational Cooling Dynamics In the Ground Statementioning
confidence: 99%
“…The band at 1663 cm −1 is assigned to the carbonyl stretching vibration, and the bands in the 1600–1520 cm −1 region can be described as collective in‐plane purine ring vibrations. The band at 1579 cm −1 comes from the imidazole ring and has a strong contribution of the C–N stretching of the pyrimidine ring whereas the shoulder at 1566 cm −1 is mainly due to the pyrimidine ring with a significant contribution from the C–NH 2 group 29 . The IR spectrum of 12‐2‐12Br 2 + GMP‐Na 2 mixture in D 2 O (10 mM) shows marked modifications from that of the unassociated GMP.…”
Section: Resultsmentioning
confidence: 94%
“…The band at 1579 cm −1 comes from the imidazole ring and has a strong contribution of the C-N stretching of the pyrimidine ring whereas the shoulder at 1566 cm −1 is mainly due to the pyrimidine ring with a significant contribution from the C-NH 2 group. 29 The IR spectrum of 12-2-12Br 2 + GMP-Na 2 mixture in D 2 O (10 mM) shows marked modifications from that of the unassociated GMP. The carbonyl band shifts to higher wavenumbers (ca.…”
Section: Self-association Of the Gmpmentioning
confidence: 97%
“…TRIR spectra recorded with excitation at 295 nm, a wavelength that is expected to excite O and not A ( (17). Absolute integrated absorption coefficients from the calculations were scaled by a constant factor that gave the best agreement with the experimental cross-sections for the O and A fundamentals.…”
Section: Resultsmentioning
confidence: 99%